Crystal structure and optical properties of non-vacuum solution-based processed Cu2ZnSnS4 (CZTS) thin-film. Issue 1 (February 2021) - Nugroho, H S; Refantero, G; Prima, E C; Panatarani, C; Suyatman,; Nugraha, N; Yuliarto, B
Abstract: Cu2 ZnSnS4 (CZTS) material has emerged as an attractive material for the absorber layer in solar cells application. CZTS has similar properties with its successful predecessor CIGS, but CZTS offers the advantage of low-cost constituents, material abundance, and nontoxicity. We fabricated CZTS thin-film using non-vacuum solution-based process and then the deposition process using the spin-coating technique in the present work. Afterward, we observed that the CZTS thin-film was successfully fabricated with kesterite structure crystal with an optical bandgap of 1.56 eV. We also confirmed that the CZTS thin-film exhibit a high light-harvesting efficiency at a low wavelength suitable for the solar cells application's absorber layer.